Resistance Response of the Recently Discovered Species Nicotiana mutabilis to Potato virus Y (PVY) and Tomato spotted wilt virus (TSWV) Compared to Other Sources of Resistance - Anna Depta; Teresa Doroszewska; Anna Czubacka (Agronomy, 2021)
Nicotiana mutabilis is a recently discovered species within the genus Nicotiana. The aim of the present study was to evaluate its resistance to Potato virus Y (PVY) and Tomato spotted wilt virus (TSWV). Molecular analysis was performed to detect the Va gene determining susceptibility to PVY and the SCAR marker associated with resistance to TSWV. Resistance tests were carried out under greenhouse conditions through artificial inoculation with one TSWV and two PVY isolates. In order to confirm the presence of the viruses in plants, DAS-ELISA tests were performed using antibodies against PVY and TSWV. The results indicated the absence of the PVY susceptibility gene and the presence of the TSWV resistance gene in the genome of N. mutabilis. This species was considered tolerant to the two PVY isolates tested because, despite the positive DAS-ELISA results, the infected plants showed vein clearing and chlorotic spots but no vein necrosis. As a result of TSWV inoculation, N. mutabilis showed a hypersensitive response; however, after four months, 30% of the inoculated plants showed systemic infection. This species extends the genetic variation in the genus Nicotiana and, because of its tolerance to PVY and partial resistance to TSWV, it may be a potential source of resistance to these viruses.